Seasonal oxygen isotope variations in freshwater bivalve shells as recorders of Amazonian rivers hydrogeochemistry. Issue 6 (2nd November 2019) - Gaillard, Blandine; Lazareth, Claire E.; Lestrelin, Hugo; Dufour, Elise; Santos, Roberto V.; Freitas, Carlos E. C.; Pouilly, Marc
ABSTRACT: Freshwater bivalve shell oxygen isotope values ( δ 18 OS ) may act as a recorder of river δ 18 O variations that can then be interpreted in terms of hydrology (e.g. precipitation–evaporation balance, precipitation and river discharge patterns). We investigated the potential of this proxy measured across the hinge of South American unionid shells: Anodontites elongatus collected in Peru and A. trapesialis in Brazil. The isotopic signatures were reproducible between individuals of the same species. A. trapesialis clearly showed a strong δ 18 OS cyclicity in accordance with its growth patterns while A. elongatus presented less clear δ 18 OS with lower amplitude. We confirm that the deposition of successive growth lines and increments is annual, with growth line corresponding to the wet season. Also, we suggest that low amplitude of δ 18 OS in the A. elongatus shells indicates a habitat close to the river while large amplitude of δ 18 OS cycles observed in A. trapesialis shells would reflect a floodplain lake habitat, seasonally disconnected from the river and thus subjected to higher seasonal fluctuations in water δ 18 O. Considering these promising first results, future studies could be directed towards the use of fossil shells to reconstruct the past and present hydrological and geochemical conditions of the Amazon.